1992
DOI: 10.1097/00006123-199207000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Operative and Excess Long-term Mortality in 935 Patients with Intracranial Meningioma

Abstract: Between 1953 and 1980, a total of 935 patients underwent surgery for intracranial meningioma in the Department of Neurosurgery of the Helsinki University Hospital. The patients were followed up until death or the end of the year 1987. The cumulative observed survival rate was 91% at 3 months, 89% at 1 year, and 63% at 15 years. The relative survival rate, that is, the ratio of the the observed and the expected rates, was 91% at 3 months, 89% at 1 year, and 78% at 15 years. Significant risk factors for operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 29 publications
1
91
0
6
Order By: Relevance
“…Lastly, there were no significant differences in incidence rates between Hispanic and non-Hispanic ethnic groups except for WHO II meningiomas, in which a slightly higher incidence was associated with non-Hispanic ethnicity (IRR 0.90; P ¼ .024) ( 18 One population-based Australian study from 2000 -2008 found a slightly higher proportion of atypical meningiomas. 19 No prior studies have reported an age-adjusted incidence rate for WHO II/III meningiomas.…”
Section: Kshettry Et Al: Epidemiology Of High-grade Meningiomasmentioning
confidence: 94%
“…Lastly, there were no significant differences in incidence rates between Hispanic and non-Hispanic ethnic groups except for WHO II meningiomas, in which a slightly higher incidence was associated with non-Hispanic ethnicity (IRR 0.90; P ¼ .024) ( 18 One population-based Australian study from 2000 -2008 found a slightly higher proportion of atypical meningiomas. 19 No prior studies have reported an age-adjusted incidence rate for WHO II/III meningiomas.…”
Section: Kshettry Et Al: Epidemiology Of High-grade Meningiomasmentioning
confidence: 94%
“…23,24 Recurrence is also related to tumor size and extent of resection: tumors that have been completely resected have a recurrence rate of 10% to 30% at 10 years, whereas subtotally resected tumors (Simpson grade IV) have a recurrence rate of 61% at 10 years. 23,[25][26][27] Currently, meningioma metastases are found incidentally. Because virtually 100% of meningiomas in culture 15 and in vivo 5 contain somatostatin receptors, 28 and because SSTR2 and SSTR5 bind octreotide, a somatostatin analog, 29 111 In-octreotide scintigraphy can be used to identify intracranial meningiomas with high sensitivity (90%-100%).…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative observed survival rate of 935 patients who underwent surgery for intracranial meningioma (operated on between 1953 and 1980) was 91% at 3 months, 89% at 1 year and 63% at 15 years (Kallio et al, 1992). Significant risk factors for operative mortality (7%) for the 652 patients (operated on from 1966 to 1980) were poor preoperative clinical condition, absence of epilepsy, old age, incomplete tumor removal, pulmonary embolism and intracranial hematoma requiring evacuation.…”
Section: Surgical Morbidity and Mortalitymentioning
confidence: 99%